Dějiny divadla jako návrh ozdravné změny paradigmatu - Pavel Janoušek (Česká Literatura)
The review of the Czech translation of the publication History of Theatre - Introduction (2022) characterizes and analyses the demand for a transformation of the theatrehistorical paradigm as proposed by Andreas Kotte. The author of the review perceives Kotte’s “introduction” as an expression of a trend shaping contemporary thinking about theatre, and therefore seeks to name the axiology, logic and limits of the argumentation Kotte works with, the inspirational power, but also the limitations of the theses he formulates. The purpose of the review is to expose, the inspiration but also the possible weaknesses of a more general transformation of views on the social role of theatre, theatre production and theatre operation.